Impact of improved indoor air quality in Nunavik homes on children's respiratory health. (23rd February 2022) - Poulin, Patrick; Marchand, Axelle; Lévesque, Benoît; Dubé, Marjolaine; Aubin, Daniel; Ouazia, Boualem; Duchaine, Caroline; Brisson, Mario
Abstract: Between 2007 and 2012, hospitalization rate related to respiratory system diseases in children ≤1–year‐old was near 7 times higher in Nunavik compared with the whole province of Quebec. To assess the impact of poor indoor air quality (IAQ) in residential environments on children's respiratory health, the Nunavik's intervention study investigated the impact of the optimization of ventilation systems on the incidence rates of respiratory infections in children in Nunavik. Children under 10 years were recruited and categorized according to the type of ventilation system in their home: energy recovery ventilator (ERV), heat recovery ventilator (HRV), no HRV or ERV, and control groups. Children's' medical records were analyzed over a period of 50 weeks pre‐ and post‐intervention. Clinical diagnoses were classified into 4 categories: upper respiratory infections, lower respiratory infections, otitis media, and asthma. A decrease in respiratory infections episodes was observed in all groups following intervention with the highest impact observed for HRV systems (−53.0%). Decreases in the ERV group were not significant (−21, 7%) possibly due to the presence of some volatile organic compound (such as propylene glycol) and inerrant experimental bias. Nevertheless, no significant association was found between health episodes incidence and household's behaviors or IAQ.